Pengaruh Manajemen Kesiswaan terhadap Prestasi Belajar Peserta Didik di SMPN 1 Pamijahan Bogor - Ihsan, Muzhir; Sumiyati, Sumiyati (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
The background of this research lies in the importance of effective student management as a strategic component in improving students' learning outcomes. Schools play a vital role not only in delivering academic content but also in managing students’ overall development, which in turn affects their academic performance. This research aims to determine whether student management practices significantly impact students' academic achievement, both partially and simultaneously. The research employed a quantitative approach with simple random sampling involving sixty respondents. Data were collected through a Likert-scale questionnaire and analyzed using several statistical techniques, including validity and reliability tests, classical assumption testing, regression analysis, correlation coefficient analysis, coefficient of determination, and hypothesis testing. The findings revealed that student management has a significant and positive influence on academic achievement. This indicates that better implementation of student management contributes to higher student performance. However, the contribution, while meaningful, suggests that other factors also influence learning outcomes. The study implies that schools should enhance student management strategies to maximize academic success.